Intellectual Brilliance: Patents and Copyrights in Publications - Dipti Shukla; M. P Chavadannavar; Anand Muchandi; Melvin David (International Journal of Sustainability, 2024)
Intellectual property rights play a vital role in safeguarding creativity and innovation, with copyrights and patents being fundamental tools in this process. This study offers an in-depth exploration of these concepts, focusing on their processes, importance, and practical applications, particularly within the healthcare sector. By delving into the nuances of intellectual property, provides valuable insights into how these rights empower creators and innovators to protect their contributions and further global progress.The presentation begins by examining the process of securing patents, detailing the step-by-step journey from conceptualization and documentation to filing, examination, and approval. This meticulous process not only ensures that original ideas receive recognition but also creates an environment that fosters innovation. It emphasizes how patents serve as a catalyst for creativity by providing legal protection that motivates inventors to develop novel solutions without fear of exploitation with a specific focus on healthcare, the presentation highlights real-world examples of patented innovations that have significantly advanced medical science. From revolutionary drug formulations and innovative medical devices to state-of-the-art diagnostic tools, these examples illustrate the transformative impact of intellectual property protection on healthcare delivery. This study also discusses how patented technologies contribute to better patient outcomes by enabling the development of more effective and accessible treatments.Furthermore, the presentation underscores the broader implications of intellectual property rights in driving scientific progress and fostering economic growth. By encouraging investment in research and development, these rights play a critical role in sustaining competitive markets and advancing societal well-being. This study explores patents and copyrights not only highlights their practical significance but also serves as a call to action for industries and individuals to prioritize the protection of intellectual property, ultimately supporting innovation and global advancement.
Keywords: Intellectual brilliance; Patents in publication; copyright publication; patented inventions